2021
DOI: 10.1021/jacs.0c13399
|View full text |Cite
|
Sign up to set email alerts
|

Unifying Concepts in Electro- and Thermocatalysis toward Hydrogen Peroxide Production

Abstract: We examine relationships between H 2 O 2 and H 2 O formation on metal nanoparticles by the electrochemical oxygen reduction reaction (ORR) and the thermochemical direct synthesis of H 2 O 2 . The similar mechanisms of such reactions suggest that these catalysts should exhibit similar reaction rates and selectivities at equivalent electrochemical potentials (μ ̅ i ), determined by reactant activities, electrode potential, and temperature. We quantitatively compare the kinetic parameters for 12 nanoparticle cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 56 publications
3
64
0
Order By: Relevance
“…Therefore, it seems plausible that catalyst performance could be rationalized by studying the HOR/ORR for thermocatalytic materials electrochemically in isolation. Supporting this hypothesis, Flaherty and co-workers investigated Au-, Pd- and Pt-based catalysts and quantitatively demonstrated the mechanistic similarities between the direct synthesis of H 2 O 2 and synchronous ORR and HOR electrochemistry 41 .…”
Section: Deriving a Common Understandingmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, it seems plausible that catalyst performance could be rationalized by studying the HOR/ORR for thermocatalytic materials electrochemically in isolation. Supporting this hypothesis, Flaherty and co-workers investigated Au-, Pd- and Pt-based catalysts and quantitatively demonstrated the mechanistic similarities between the direct synthesis of H 2 O 2 and synchronous ORR and HOR electrochemistry 41 .…”
Section: Deriving a Common Understandingmentioning
confidence: 90%
“…Intriguingly, materials such as Au or Ag possess relatively low catalytic current densities as the half-cell kinetics for the HOR are poor (hypothetically shown in Fig. 2b ) 41 . However, due to low H 2 O 2 residence time and the subsequent hindrance of oxygen adsorption, they tend to demonstrate high selectivity.…”
Section: Deriving a Common Understandingmentioning
confidence: 99%
“…[15] More thorough analyses pointed out that protic solvent at solid-liquid interfaces assists the transfer of protons and electrons to reduce oxygen. [16] Further, electro-and thermo-catalysis toward hydrogen peroxide production share an identical proton-electron transfer pathway. [17] Along the same line, Surendranath et al…”
Section: Introductionmentioning
confidence: 99%
“…27 Further, electro-and thermo-catalysis toward hydrogen peroxide production share an identical proton-electron transfer pathway. 28 By measuring the catalyst potential, Surendranath et al showed that aerobic formic acid oxidation reactions should be viewed as two electrochemical half reactions: 1) HCOOH → CO2 + 2H + + 2e -; 2) 0.5O2 + 2H + + 2e -→ H2O, in the same way as the electro-catalytic oxidation of formic acid. 29 These findings provide a quantitative and predictive link between thermo-and electro-catalytic aerobic oxidation.…”
Section: Introductionmentioning
confidence: 99%